DEVELOPMENT OF ADHA SUPPLEMENT INNOVATION (MORINGA LEAF ANTI-FATIGUE NATURAL HERBAL) AS A SUPERIOR PRODUCT OF NUSA TOURISM VILLAGE - Aditya Candra; Tahara Dilla Santi; Muhammad Faisal (International Review of Practical Innovation, Technology and Green Energy (IRPITAGE), 2025)
The Community Partnership Empowerment (PKM) program involves Family Welfare Movement (PKK) group partners. Preparation for the program began in June 2025, beginning with a visit by the implementation team to Gampong Nusa to conduct a survey to assess community conditions. During the subsequent visit, the team submitted a PKM implementation permit from LPPM UNAYA and briefly presented the PKM program. The team explained the stages of the program, the implementation schedule, and other details. Counseling and training were held on September 20, 2025, followed by mentoring in the production of ADHA products, including moringa tea, moringa powder, moringa sachets, and moringa capsules. Following the mentoring, the best and fastest group in producing ADHA products was selected. Subsequently, on September 21, 2025, the community service team planted 250 moringa cuttings in several locations in Gampong Nusa..